Communicate for a Change : Revitalizing Conversations for Higher Education - Carrell, Lori, 1962-; Zemsky, Robert, 1940- (Book collections on Project MUSE., 2021)
"This book models conversations about the difficult questions higher education now regularly avoids. It breaks new ground in terms of both its subject matter and its format, which is a set of frank and revealing conversations between two friends and colleagues who have known each other and worked together for more than a decade"--